Development and validation of a polygenic risk score for height in a Greek cohort: Association with blood pressure measurements - Kalafati, Ioanna Panagiota; Tsifintaris, Margaritis; Dimitriou, Maria; Grigoriou, Effimia; Moulos, Panagiotis; Dedoussis, George V. (Frontiers in Genetics, 2025)
Human height is a highly heritable trait. Genome-wide association studies have identified thousands of genetic variants linked to height, some of which exhibit pleiotropic effects. However, population-specific genome-wide Polygenic Risk Scores (PRSs) for height for specific populations remain limited. In this study, we developed a PRS for height tailored to Greek individuals using a dataset of 1970 adults. We applied a robust, iterative PRS construction pipeline based on previously published methods to capture the unique genetic architecture of height in this population. Our analysis identified multiple significant heightassociated SNPs specific to the Greek population and the constructed Greek-specific PRS accounted for 10.8% of height variability. A significant overlap of height-associated SNPs with those of generalized PRSs from other European populations constitutes a positive marker for our methodology. Additionally, the PRS was associated with blood pressure, aligning with evidence from other studies. These results highlight the importance of applying a rigorous methodology in PRS derivation. This is the first genome-wide height-PRS for Greek adults, which may serve as a foundation for further studies on genetic risk prediction and personalized healthcare in underrepresented populations.